Genotoxicity effects of nano bioactive glass and Novabone bioglass on gingival fibroblasts using single cell gel electrophoresis (comet assay): An in vitro study - Tavakoli, Mohammad (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The greater surface of bioactive glass nanoparticles presents an incomparable and promising feature similar to the biological apatite. Nanoparticles improve cellular adhesion, enhance osteoblast proliferation and differentiation, and increase biomineralization for periodontal regeneration and dental implants. Considering the fact that interaction between periodontal cells and bone graft materials are important for periodontal lesion regeneration, the present study was undertaken to investigate the genotoxicity of a novel synthesized nanoscale bioactive glass and compared it with Novabone bioglass in periodontal fibroblasts cells, in order to approve the biocompatibility of nano bioactive glass. MATERIALS AND METHODS: In this in vitro experimental study, periodontal C165 fibroblasts cells were cultured in their logarithmic phase and the genotoxicity of novel synthesized bioactive glass nanoparticles and Novabone bioglass was studied in different concentrations and a control group using Comet assay test. By using Autocomet software, three parameters (Tail length, %DNA in tail, Tail moment) were analyzed; the genotoxicity of mentioned biomaterials and control group. Obtained data were analyzed by SPSS 11.5 software, Kruskal Wallis H and Mann Whitney tests (P = 0.05). RESULTS: No statistically significant difference was observed between the concentrations of Novabone bioglass (P value = 0.085) with control group and novel nano bioactive glass (P value = 0.437) with control group in the evaluation of %DNA in tail parameter. There was significant difference between genotoxicity of novel nano bioactive glass and control, and between Novabone bioglass and control group in concentrations of 4 and 5 mg/ml. According to significance of the mean difference, novel nano bioactive glass showed higher genotoxicity compared to Novabone bioglass in the concentration of 5 mg/ml (P ≤ 0.05). CONCLUSION: The findings of this study have demonstrated that novel nano bioactive glass had no genotoxicity in concentrations lower than 4 mg/ml. Nanoparticles have a higher surface area in comparison to microparticles and thus, the amount and rate of ion release for nanoparticles are extremely higher. This difference is the main reason for the different genotoxicity of nano bioactive glass and micro Novabone bioglass in the concentrations higher than 4 mg/ml.